Highly efficient three‐dimensional solar evaporator for zero liquid discharge desalination of high‐salinity brine - Meichun Ding; Demin Zhao; Panpan Feng; Baolei Wang; Zhenying Duan; Rui Wei; Yuxi Zhao; Chen‐Yang Liu; Chenwei Li (Carbon Energy, 2024)
Abstract Solar‐driven interfacial evaporation is a promising technology for freshwater production from seawater, but salt accumulation on the evaporator surface hinders its performance and sustainability. In this study, we report a simple and green strategy to fabricate a three‐dimensional porous graphene spiral roll (3GSR) that enables highly efficient solar evaporation, salt collection, and water production from near‐saturated brine with zero liquid discharge (ZLD). The 3GSR design facilitates energy recovery, radial brine transport, and directional salt crystallization, thereby resulting in an ultrahigh evaporation rate of 9.05 kg m−2 h−1 in 25 wt% brine under 1‐sun illumination for 48 h continuously. Remarkably, the directional salt crystallization on its outer surface not only enlarges the evaporation area but also achieves an ultrahigh salt collection rate of 2.92 kg m−2 h−1, thus enabling ZLD desalination. Additionally,  3GSR exhibits a record‐high water production rate of 3.14 kg m−2 h−1 in an outdoor test. This innovative solution offers a highly efficient and continuous solar desalination method for water production and ZLD brine treatment, which has great implications for addressing global water scarcity and environmental issues arising from brine disposal.